U.K. and Global Wine Markets by 2025, and Implications of Brexit*. (10th November 2017) - Anderson, Kym; Wittwer, Glyn
Abstract: The United Kingdom has accounted for a major share of the world's wine imports for centuries, and wine accounts for more than one-third of U.K. alcohol consumption. It is therefore not surprising that suppliers of those imports and U.K. wine consumers, producers, traders, distributors, and retailers are focusing on what the United Kingdom's planned withdrawal from the European Union (Brexit) might mean for them. In this paper, a model of the world's wine markets is used to project those markets to 2025 without, and then with, the occurrence of Brexit. The Brexit scenarios involve adjustment not just to U.K. and EU27 (the countries remaining in the European Union) bilateral tariffs but also to assumed changes to the United Kingdom's income growth and currency. The relative importance of each of these three components of the initial shock are reported, as are impacts on bilateral wine-trade values and volumes for still and sparkling wines. The results suggest that the impact outside the United Kingdom will be minor compared with other developments in the world's wine markets. Inside the United Kingdom, however, the effect of Brexit on incomes and the British pound are likely to have nontrivial initial impacts on the domestic wine market and to be far more consequential than the direct impact of changes in bilateral tariffs. (JEL Classifications: F15, F14, F13)